2015
DOI: 10.3996/012014-jfwm-003
|View full text |Cite
|
Sign up to set email alerts
|

Local and Landscape Habitat Associations of Shorebirds in Wetlands of the Sacramento Valley of California

Abstract: The Sacramento Valley of California is a site of international importance for shorebirds despite having lost >90% of its historic wetlands. Currently both managed wetlands and flooded agriculture are important habitats for shorebird populations, but the extent of flooded agriculture may be declining in early winter when shorebirds need to acquire resources postmigration to survive winter. We employed long-term shorebird monitoring data to evaluate factors influencing abundance and species richness of sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…We also assumed an ideal free distribution (Fretwell and Lucas 1969) of shorebirds across all available habitat throughout the Central Valley and our (Taft et al 2002;Reiter et al 2015b). However, changes in habitat availability during one part of the season can affect energy availability later in the season in unexpected and non-linear ways, such that a 50% increase in available habitat does not necessarily correspond to a 50% decrease in energy shortfalls.…”
Section: Research Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also assumed an ideal free distribution (Fretwell and Lucas 1969) of shorebirds across all available habitat throughout the Central Valley and our (Taft et al 2002;Reiter et al 2015b). However, changes in habitat availability during one part of the season can affect energy availability later in the season in unexpected and non-linear ways, such that a 50% increase in available habitat does not necessarily correspond to a 50% decrease in energy shortfalls.…”
Section: Research Needsmentioning
confidence: 99%
“…An extensive network of restored and managed wetlands and post-harvest flooded rice, corn, and other crops currently provide substantial habitat for non-breeding shorebirds in the Central Valley (Fleskes et al 2012;Strum et al 2013;Reiter et al 2015b). However, the timing, extent, and depth of flooding can greatly affect their value as shorebird foraging habitat (CVJV 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The restoration of previously lost or degraded tidal or nontidal wetlands, or the protection of key habitat features in tidal wetlands, have been associated with numerous benefits to wintering shorebirds. These benefits include increases in the extent of suitable foraging areas (Atkinson ; Armitage et al ; Patten & O'Casey ), including seasonally available habitat (Colwell & Dodd ; Warnock & Takekawa ); landscape position and proximity to natural wetlands (Brusati et al ; Reiter et al ); increased food supply or availability (Atkinson ; Miller & de Rivera ); reestablishment of the natural hydroperiod and water levels suitable for foraging (Bellio & Kingsford ; Brand et al ); development of roosting opportunities or other conditions that facilitate improved predator avoidance (Rogers et al ; Huang et al ); and enhancement of alternative feeding opportunities when primary foraging areas are rendered unsuitable by flooding or tidal inundation (Warnock et al ; Armitage et al ; Gomez‐Sapiens et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Reiter et al () demonstrated the importance of seasonally flooded wetlands within a 10‐km buffer (314 km 2 ) in predicting winter shorebird abundances. Their work was conducted on interior landscapes characterized primarily by seasonally flooded marshes, which may differ substantially from coastal wetlands with regard to spatial scales of variation in shorebird abundances.…”
Section: Introductionmentioning
confidence: 99%
“…Small adjustments could be made based on the feasibility of habitat restoration or the distribution of focal species most in need while maintaining viable populations in each planning region. Further, despite the strong dispersal ability of shorebirds, the spatial distribution of habitat within each planning region may also affect habitat use and subsequent achievement of density and population objectives (Reiter et al 2015). We recommend creating and restoring habitat in areas that cluster habitat and maximize connectivity of semi-permanent wetlands and other shorebird breeding habitat.…”
Section: Measuring Successmentioning
confidence: 99%